2012
DOI: 10.1002/evan.21324
|View full text |Cite
|
Sign up to set email alerts
|

Primate origins, human origins, and the end of higher taxa

Abstract: When people learn that I study human evolution and we start talking about it, they sometimes ask me, “How long ago did the first humans live?” My answer is usually another question: “What do you mean by 'humans'?” That response seems as baffling and wrong‐headed to them as their question seems to me, and it usually takes us a while to straighten things out. © 2012 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 101 publications
1
29
0
Order By: Relevance
“…Therefore, the postcranial specializations for arboreality documented in Purgatorius would have allowed this animal to access resources that were not directly available to many contemporary terrestrial mammals, such as Protungulatum. The fossil record provides a direct test to evaluate adaptive scenarios, however incremental (8), and future recovery and analysis of early euarchontan fossils will continue to improve our understanding of primate origins. The previously unidentified fossils of Purgatorius described here suggest that the divergence of primates from other mammals was not a dramatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the postcranial specializations for arboreality documented in Purgatorius would have allowed this animal to access resources that were not directly available to many contemporary terrestrial mammals, such as Protungulatum. The fossil record provides a direct test to evaluate adaptive scenarios, however incremental (8), and future recovery and analysis of early euarchontan fossils will continue to improve our understanding of primate origins. The previously unidentified fossils of Purgatorius described here suggest that the divergence of primates from other mammals was not a dramatic event.…”
Section: Discussionmentioning
confidence: 99%
“…Plesiadapiforms, a geographically widespread radiation of Paleogene mammals , are the only group of fossils widely regarded as probable stem primates (Simpson, 1935;Gingerich, 1976;Szalay and Delson, 1979;Szalay et al, 1987;Bloch and Boyer, 2002;Janecka et al, 2007). Though various researchers remain skeptical about plesiadapiforms as stem primates [see Godinot (2007)] and some well-sampled cladistic analyses contradict this idea (e.g., Ni et al, 2013), plesiadapiforms are universally regarded as members of Euarchonta, a group whose extant members include primates, dermopterans (Cynocephalus and Galeopterus, the "flying lemurs"), and scandentians (Tupaiidae and Ptilocercidae, the treeshrews) (Szalay and Decker, 1974;Szalay and Delson, 1979;Szalay and Dagosto, 1980;Szalay and Drawhorn, 1980;Szalay et al, 1987;Bloch and Boyer, 2002;Cartmill, 2012). At the very least, plesiadapiforms are the only euarchontans with a sampled postcranial fossil record just prior to the appearance of taxa usually assumed to be members of euprimates.…”
Section: Fossil Taxa Reviewed: Systematic Considerationsmentioning
confidence: 99%
“…These disagreements in the literature are further compounded by two classification systems, clades and grades, which are used interchangeably in the naming of genera. While supraspecific taxa may prove to be obsolete in future years (Cartmill, 2012), both clades and grades are immensely useful in describing evolutionary and adaptive histories. Hence, the present author calls for more rigorous definitions to be used in hominin systematics, possibly with two parallel classification systems, clades and grades, that remain distinct in their objectives, clades to describe the route of evolution and grades to describe the product (Wood and Lonergan, 2008), but that each can be separately used to communicate our understanding of hominin evolution and adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cartmill (2012) has suggested that all supraspecific taxonomy may be found entirely superfluous. Cartmill suggests that parallelisms are inevitable in closely related taxa due to the similarities in their morphology and the selective pressures that are exerted upon them.…”
Section: How Should Species Be Classified Into Higher Taxa?mentioning
confidence: 99%
See 1 more Smart Citation